Evaluation of Stocking Density and Dietary Fish Meal Inclusion for Intensive Tank Production of Pacific White Shrimp Litopenaeus vannamei Cultured in Low‐Salinity Waters of Western Alabama. (5th May 2020) - Roy, Luke A.; Teichert‐Coddington, David; Beck, Benjamin H.; Dahl, Sunni; James, Jesse; Guo, Jingping; Davis, D. Allen
Abstract: Shrimp farmers in Alabama are seeking to increase efficiency and intensify production. Semi‐intensive earthen ponds are the traditional production system used by Alabama shrimp farmers; however, there is interest in evaluating intensive pond‐based production systems, such as split ponds. These alternative systems are more intensive and require higher stocking densities to offset capital investment costs required for initial construction and maintenance. Two trials were carried out with Pacific white shrimp Litopenaeus vannamei using on‐levee flow‐through systems (twelve 800‐L tanks per system) at an Alabama shrimp farm to evaluate stocking densities of 29, 88, 176, and 264 shrimp/m 2 (trial 1) and higher levels of fish meal (5, 10, and 20%) at a high density of 264 shrimp/m 2 (trial 2). Results from trial 1 revealed that as stocking density was increased Pacific white shrimp final weight decreased, while shrimp biomass and feed conversion ratio increased. Survival of Pacific white shrimp at the two highest densities (176 and 264 shrimp/m 2 ) was lower than at the two lowest densities (29 and 88 shrimp/m 2 ). There were no significant differences in performance for Pacific white shrimp offered diets with varying levels of fish meal in trial 2; however, overall survival in trial 2, which was carried out at a high density (264 shrimp/m 2 ), ranged between 47.9% and 65.5%.